Stock Valuation on the example of KMG - Bolturukova, D.; Manapova, M.; Shadykhanova, U.; Yermekbay, D. (Maqsut Naribayev University International School of Economics, 2023)
This particular research is focused on stock valuation on JSC NAC “KazMunayGas”. The Initial Public Offering process started in recent years, and has gained a lot of public attention and support. The KMG is a leading company in the oil and gas center with a stable strategic development. Incorporating data from financial statements, articles and graphs, this research paper demonstrates that KMG has a stable and promising example of integrating innovation into production processes and management decisions. This paper examines the process and results of stock offering by financial statements analysis and valuation model. The implemented Discounted Cash Flow model is a tool for evaluating the fair share price with the use of relevant sources like Bloomberg, Damodaran and financial reports of the Company. It contains different tables and graphs, which cover the valuation model, external analysis and management analysis for deeper research and reliability of results. Main purpose of the research is to apply theoretical and practical skills on actual examples and provide the proper investment decision and business valuation analysis
Keywords: oil and gas industry, JSC NAC “KazMunayGas”, valuation model, Initial Public Offering (IPO), management decision